Regulated expression of cytokines in human endometrium throughout the menstrual cycle: dysregulation in habitual abortion - Wolff, Michael von; Thaler, C. J.; Strowitzki, Thomas; Broome, J.; Stolz, W.; Tabibzadeh, S. (Molecular human reproduction, 2000)
It is widely assumed that, after ovulation, the human endometrium undergoes specific changes and becomes receptive to the implantation of embryo during the mid-secretory phase. When implantation does not take place, further changes occur which eventually result in the shedding of human endometrium. The present study was carried out to examine whether there are changes in the cytokine gene expression in human endometrium which are correlated with endometrial function in various phases of the menstrual cycle.